Devising a combined spectrum spreading method for timer signal structures to improve covert information transmission - Stepanov, Vadym; Korchynskyi, Volodymyr; Kildishev, Vitalii; Zarovskyi, Ruslan; Havel, Serhii; Slavych, Vasyl; Petrovskyi, Ruslan (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process that forms noise-like timer signal structures with combined spectrum spreading in secure radio communication systems. The work addressed the scientific and technical problem related to the lack of methods for forming noise-like signal structures that provide comprehensive use of the advantages of timer coding, direct spectrum spreading, as well as pseudo-random tuning of the operating frequency, in order to improve covert structure and noise immunity of information transmission. The results include a combined method devised for spectrum spreading of non-positional timer signals based on a combination of direct spectrum spreading and pseudo-random tuning of the operating frequency. The method provides spectrum spreading in the time and frequency domains, as well as the generation of multidimensional signal structures by varying the time intervals between pulses, using pseudo-random sequences, and tuning of the operating frequencies. An analytical approach to assessing covert structuring of a combined signal has been proposed, taking into account the parameters of timer coding, manipulation, and spectrum spreading. It was established that even with relatively small values of the signal parameters, a high level of structural covertness was achieved, which significantly complicated its reproduction by means of electronic reconnaissance. The results are attributed to the combination of timer coding with spread spectrum methods, which ensured the generation of time, code, and frequency uncertainty of the signal. Changing the timer coding parameters made it possible to adapt signal structures depending on the level of interference in the communication channel. The proposed method could be implemented when designing promising secure radio communication systems under conditions of random and intentional interference